2016
DOI: 10.1038/ncb3312
|View full text |Cite
|
Sign up to set email alerts
|

Organoids as an in vitro model of human development and disease

Abstract: The in vitro organoid model is a major technological breakthrough that has already been established as an essential tool in many basic biology and clinical applications. This near-physiological 3D model facilitates an accurate study of a range of in vivo biological processes including tissue renewal, stem cell/niche functions and tissue responses to drugs, mutation or damage. In this Review, we discuss the current achievements, challenges and potential applications of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
998
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,173 publications
(1,018 citation statements)
references
References 91 publications
8
998
0
12
Order By: Relevance
“…We found that SCLT neurons could internalize the FM1‐43 fluorescent dye following an initial dose of high [K + ] and release it after a second dose ( Figure 3 a–c). This is consistent with the fashion of mature neurons in FM dye loading and releasing following high [K + ] stimulation 14. Ca 2+ oscillations activity could be detected when neurons are loaded with calcium dye 15.…”
Section: Resultssupporting
confidence: 86%
“…We found that SCLT neurons could internalize the FM1‐43 fluorescent dye following an initial dose of high [K + ] and release it after a second dose ( Figure 3 a–c). This is consistent with the fashion of mature neurons in FM dye loading and releasing following high [K + ] stimulation 14. Ca 2+ oscillations activity could be detected when neurons are loaded with calcium dye 15.…”
Section: Resultssupporting
confidence: 86%
“…Nevertheless, the in vivo cellular compartmentations and cell–cell interactions are not preserved in these systems. Recently, a stem‐cell‐based 3D tissue model, termed organoid, that better recapitulates tissue composition, architecture, and functionality has been developed 5. Organoids are in vitro 3D grown organized structures that mimic their respective organs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of Wnt signaling is associated with onset of cancer, most notably carcinoma of the colon and rectum [45]. Other studies have employed CRISPR/Cas9-mediated gene editing of healthy organoids to directly evaluate candidate gene function in tissue physiology and carcinogenesis [46].…”
Section: Organoid Disease Modeling and Transplantationmentioning
confidence: 99%
“…Despite the great advances in the field of intestinal organoids, the great challenge is, as described by Fatehullah et al [46], to rapidly and safely translate the knowledge of mouse stem cells into the human arena. Efforts to exploit intestinal stem cells for regenerative medicine have accelerated over the past decade, driven mostly by the identification of cell-surface markers facilitating the isolation of pure stem cell populations and the development of near-physiological culture methods supporting stem cell expansion and epithelial growth.…”
Section: Future Of Organoids In Veterinary Medicinementioning
confidence: 99%